Development of a Research-Based Module on the Variation of Nepenthes miriabilis (L) Druce in Various Habitats for the Lesson of Plant Taxonomy - Aswin, Pani; Irawati, Mimien Henie; Saptasari, Murni (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Modules are teaching materials that provide independent learning experiences and increase studentcompetence effectively. The purpose of this research is to develop a research-based module on the variationof Nepenthes miriabilis (L) Druce in various habitats for plant taxonomy courses. The research design usedis research and development. The development results consist of 1) potential analysis consisting of a highdiversity of Nepenthes miriabilis (L) Druce and no research-based modules have been applied; 2) moduledesign consisting of cover, learning activities and assessments; 3) the validation test shows that the moduleassessment obtained from material experts is 98.4% very valid and field trials can be carried out. The resultsof the assessment of the Plant Taxonomy module based on the media aspect amounted to 96.87% with avery valid category and worthy of field trials